Manfaat Jintan Hitam (Nigella sativa) sebagai Antiinflamasi dan Pereda Nyeri pada Osteoartritis (OA) - Chanief Hassan Widjaja (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Osteoarthritis (OA) is a disease that is often found in all parts of the world. OA often affects women or men, especially those who are elderly. It’s not uncommon for people with OA to complain the intensity of pain due to the disease. OA is a degenerative bone disease that is often associated with joint cartilage damage in patients. Although OA was originally referred to as a non-inflammatory joint disease, several studies have shown that OA can occur due to chronic inflammation that underlies the disease. Several studies have shown that the inflammatory cytokines IL-1β and TNF-α play an important role in the pathogenesis of OA. Untreated OA will lead to the patient’s disability. Nigella sativa or black cumin is a herbal plant that is often used as an anti-inflammatory drug for various diseases, including osteoarthritis. Nigella sativa produces thymoquinine compounds which can act as anti-inflammatory and anti-proliferative compounds in OA. The research method for this article is a literature review from books, various national and international journals in the period 2010 until 2020. The study results show that Nigella sativa potentially acts as an anti-inflammatory and pain reliever in OA patients.